Frasa Endosentris dan Eksosentris pada Penyampaian Visi Misi Capres 2024 dalam Debat Pertama - Langoday, Yohanes Redan; Mora, Octadita Grace; Nensilianti, Nensilianti (Universitas Muhammadiyah Surabaya, 2024)
The subject of this study is to analyze the use of endocentric and exocentric phrases contained in the implementation of the vision and mission of the 2024 presidential candidates. The purpose of this research is to analyze the use of endocentric and exocentric phrases included in the presidential candidates' vision-mission presentation. The research method used in this research is a qualitative method using listening and recording techniques. The research data to be obtained are endocentric and exocentric phrases used by each presidential candidate in implementing the vision mission. The data source of this research comes from the YouTube video streaming platform of the official KompasTV channel. In implementing the vision and mission of the presidential candidates, the researcher arrived at the following research results. First, endocentric phrases have different types based on word structure, namely coordinative, attributive, and appositive endocentric phrases. Meanwhile, exocentric phrases have different types based on word structure, namely directive and non-directive exocentric phrases. Second, every phrase that the presidential candidates use in expressing their vision and mission is included in the existing phrase classifications, although not all of them.